Evaluating CASPASE-9 Gene Expression and Protein Level in Iraqi Patients with β-Thalassemia Major - Abbas, Reyam Mohammed; Al-Saffar, Jinan Mohammed Jawad (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: Caspase-9 (CASP9) is a cysteine-dependent, aspartate-specific protease primarily recognized for its role in apoptosis. It functions as an initiator caspase in the intrinsic (mitochondrial) pathway of apoptosis, leading to programmed cell death. Objectives: To assess the gene expression of CASP9 and its protein level in β-thalassemia major (β-TM) patients compared to healthy controls. Methods: The study included 100 participants, 50 of whom had β-TM, whereas the other 50 served as controls. To assess the CASP9 transcript levels, blood samples were collected from each participant, and RNA extraction was performed. cDNA synthesis was carried out, and real-time PCR was utilized for the analysis. Results: No statistically significant difference was observed in the age distribution between the β-thalassemia major (β-TM) patients and the healthy controls (p>0.05), with a mean age of 15.58 and 15.24 years, respectively. The gender was comparable between groups (p>0.05), indicating that the groups were well-matched. The CASP9 gene was significantly overexpressed in β-TM patients, with a fold change of 2.04 compared to 1.0 in controls. Gene expression was quantified using quantitative real-time PCR (qRT-PCR), while protein levels were measured using enzyme-linked immunosorbent assay (ELISA). A positive correlation was observed between CASP9 mRNA expression and its corresponding protein levels (r=0.489, p<0.0001). Conclusions: CASP9 was overexpressed in β-TM patients and was positively correlated with its protein level, indicating that transcriptional upregulation is associated with increased protein expression in β-TM patients.